Aging Society and Attitude to Risk - Kuti, Mónika; Schepp, Zoltán (Public Finance Quarterly, 2020)
The objective of this study fills a gap in the Hungarian academic literature: its goal, on the one hand, is to systematise the research trends of decision-making and risk preferences at older ages according to the various methodological approaches, including researches based on experiment, questionnaire or wealth portfolio holding, and, on the other hand, to identify the impacts between age and financial literacy. The international academic literature shows that the researches on attitude to risk at older ages reached different conclusions depending on the research method used. In an experimental environment embedded in a play situation older people are rather risk-seeking, whereas in case of learning leading to a risky choice they are risk-averse. Based on the conclusion drawn from questionnaire surveys and portfolio selection methods, willingness to take risks decreases in older cohorts. The risk preferences dynamically changing with age highlight a new dimension of investment decisions. The research of the relationships between the investment experience accumulated with increasing age – which raises risk tolerance – and the cognitive abilities deteriorating as the end of the life-cycle approaches highlights several contradictions in the international literature.